Narrating Wonder in Mark Anthony Jarman’s Stories - Blake, Jason (Text Matters: A Journal of Literature, Theory and Culture, 2022)
Mark Anthony Jarman’s characters are often down and out, and often wandering and wondering. Using theories of wonder, this essay argues that wonder plays a key role in many of Jarman’s stories—stories that are marked not by narrative or psychological closure, but by a sense of wonder as characters muse on their lot in life. After briefly considering Jarman’s role within Canadian literature, including his innovative approaches to the short story form, and his odd status as an influential yet often ignored writer, the essay moves to a discussion of the various ways that wonder is at play in his works, both as a verb and a state. Jarman’s characters are frequently in doubt, and the act of wondering takes us into their drifting, self-reflecting minds. However, there is also the sense of wonder as the miraculous. Jarman’s narrators find optimism in the world around them, thanks to flashes of the beauty of the unlikely. Wonder, thus, has a crucial structural function.